2015
DOI: 10.1097/mib.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Levels of MicroRNA-19 Are Associated with a Stricturing Crohnʼs Disease Phenotype

Abstract: These data identify miR-19-3p as a potential circulating marker of stricturing CD. Our data show that microRNAs have utility as noninvasive biomarkers of stricturing CD. Further longitudinal studies are required to determine the prognostic value of miR-19-3p at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…In addition, its decreased serum level has been reported in association with intestinal fibrosis [36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its decreased serum level has been reported in association with intestinal fibrosis [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of miR-142-3p were associated with the presence and severity of scleroderma, an autoimmune disease that causes a progressive fibrotic tissue formation in the normal tissue architecture of various organs [36,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Polytarchou and colleagues reported that serum miR-223-3p, miR-4454, miR23a-3p, and miR320e levels correlated with UC disease activity better than serum C-reactive protein levels [46]. Lewis et al identified miR-19a-3p and miR-19b-3p as markers of stricturing CD, both miRNAs were expressed at lower levels in the serum of CD patients with strictures in comparison to non-stricturing CD patients [39]. …”
Section: Circulating Mirna Expressionmentioning
confidence: 99%
“…20 MiR-19a-3p and miR-19b-3p are reduced in the serum of stricturing Crohn's disease patients compared with that of nonstricturing Crohn's disease. 21 Moreover, according to a multivariate analysis, the association between miR-19-3p and stricturing phenotype is independent of confounding clinical variables including ileal location and disease duration. 21 …”
Section: Mirsmentioning
confidence: 99%
“…21 Moreover, according to a multivariate analysis, the association between miR-19-3p and stricturing phenotype is independent of confounding clinical variables including ileal location and disease duration. 21 …”
Section: Mirsmentioning
confidence: 99%